Balancing women's rights with the practice of Islam: case studies of Turkey and Iraq - Casey, Leora (My University, 2011)
Islamic women’s rights remain a widely contested issue within the international relations discourse. This research attempts to address this issue by examining Islamic women’s rights in Turkey and Iraq. Balancing women’s rights with the practice of Islam: Case studies of Turkey and Iraq, discusses the balance that Turkey has achieved between women’s rights and the practice of Islam with the aid and discussion of postcolonial feminism and Islamic feminism. This research then examines the case of Iraq, a state currently seeking international recognition. Iraqi women’s rights are examined in an attempt to pinpoint whether factors that enabled Turkey’s success can be found in Iraq. This research then identifies and analyses such factors, by concluding on the future of women’s rights and the practice of Islam in both Turkey and Iraq.